FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI MANAJEMEN BISNIS SYARIAH UMSU - Arbaini, Nurul Putri; Afandi, Ahmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the elements that influence UMSU Sharia Business Management students’ interest in entrepreneurship. As independent variables, emotional intelligence (X1), entrepreneurial knowledge (X2), and family environment (X3) were studied. Where entrepreneurial interest (Y) is the dependent variable. This research is quantitative and survey-based. The survey was conducted on 42 UMSU Sharia Business Management students class of 2020. Data was analyzed using multiple linear regression to evaluate the impact of factors. This research found that 1) emotional intelligence, entrepreneurial knowledge, and family environment simultaneously have a significant effect on UMSU Sharia Business Management students’ entrepreneurial interest, 2) partial emotional intelligence has no effect, 3) partial entrepreneurial knowledge has a significant effect, and 4) family environment partially does not have a significant effect.